Effect of rumen degradability of protein and fat on the growth and development of dairy calves - D.E. Isbell; J.L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1990)
Sixty heifer and 34 bull calves were fed starter diets containing either control or extruded soybean meal (SBM) and either 2.5% or no bypass fat from birth to 8 wk of age. There were no interactions between the type of SBM and the amount of fat. There were no significant differences between the calves fed control or extruded SBM with or without fat supplementation, although the trends favored the calves fed extruded SBM with no bypass fat.; Dairy Day, 1990, Kansas State University, Manhattan, KS, 1990; The 1990 Annual KSU Dairy Day is known as Dairy Day, 1990
Keywords: Dairy Day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-148-S; Report of progress (Kansas Agricultural Experiment Station); 608; Rumen degradability; Protein; Fat; Growth; Dairy calves